The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fgene.2022.1018632
|View full text |Cite|
|
Sign up to set email alerts
|

Population genetics analysis of Tolai hares (Lepus tolai) in Xinjiang, China using genome-wide SNPs from SLAF-seq and mitochondrial markers

Abstract: The main topic of population genetics and evolutionary biology is the influence of the ecological environment, geographical isolation, and climatic factors on population structure and history. Here, we estimated the genetic diversity, genetic structure, and population history of two subspecies of Tolai hares (Lepus tolai Pallas, 1778), L. t. lehmanni inhabiting Northern and Northwest Xinjiang and L. t. centrasiaticus inhabiting Central and Eastern Xinjiang using SNP of specific-length amplified fragment sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Unlike previous studies on Asian Artemia (Kappas et al, 2011;Eimanifar et al, 2015), our results suggest that the genetic structure of Artemia in Tibet is more complex. The selection of the best K value for crossvalidation must be performed carefully, and multiple datasets, such as phylogenetic trees and PCA, should be combined to determine the final genetic structure of the species (Liu et al, 2022;Mamat et al, 2023). Population structure analyses showed that ten 10 populations from different regions of China could be classified into four geographically and genetically distinct groups.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies on Asian Artemia (Kappas et al, 2011;Eimanifar et al, 2015), our results suggest that the genetic structure of Artemia in Tibet is more complex. The selection of the best K value for crossvalidation must be performed carefully, and multiple datasets, such as phylogenetic trees and PCA, should be combined to determine the final genetic structure of the species (Liu et al, 2022;Mamat et al, 2023). Population structure analyses showed that ten 10 populations from different regions of China could be classified into four geographically and genetically distinct groups.…”
Section: Discussionmentioning
confidence: 99%